2020
DOI: 10.4236/jmmce.2020.84011
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical and Mechanical Characterization of the Bast Fibers of <i>Triumfetta cordifolia</i> A.Rich. from the Equatorial Region of Cameroon

Abstract: The project consists in the implementation of a biocomposite based on tannin resin and natural rubber matrices with the bast fibres of Triumfetta cordifolia A.Rich. "Okong" from the equatorial region of Cameroon as reinforcement. A study of this still little known fibre is necessary. This paper evaluates the physico-chemical and mechanical characteristics of the fibers. The fibers are extracted by us. A series of experiments is conducted for this purpose: morphological observation with a scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
2
22
2
Order By: Relevance
“…The real density was determined with the technique of helium pycnometry as described in [10]. The obtained value was verified by an evaluation of the density by the simple Rule of Mixture (ROM) by applying Equation (1).…”
Section: Densities and Porosities Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The real density was determined with the technique of helium pycnometry as described in [10]. The obtained value was verified by an evaluation of the density by the simple Rule of Mixture (ROM) by applying Equation (1).…”
Section: Densities and Porosities Measurementsmentioning
confidence: 99%
“…However, with the increase of demand in green materials combined to the decrease of growing space for these common plant fibers, and the race towards new tropical species which are accessible and at lower cost, some recent scientific works have been carried out in this field. Researches enabled to study new plant fibers such as those derived from pineapple leaves (PALF) [8], Rhectophyllum camerunense roots [1], Okra stems [9], Triumfetta cordifolia [10], Sida cordifolia [11], Arundo donax [7], Lygeum spartum [4], Coccinia grandis [12] for their use as reinforcement for composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…The TGA curve revealed that enset fiber remained thermally stable up to the decomposition temperature reaching to 227 o C while this temperature raised to 264 o C with medium and highly treated enset fibers. At lower decomposition temperature ranging from 38-115 o C of raw enset and treated fine enset fibers, only the moisture present on their components were evaporated [34]. The water loss of raw fiber and medium (15% w/v) and highly (20% w/v) treated enset fibers was realized around 9 % at the initial decomposition temperature of the fibers due to evaporation of water shown in Table 1.…”
Section: Thermal Characterization Of Enset Nano Fiber (Tga)mentioning
confidence: 99%
“…Thus, works have focused on the study of the properties of new plant fibers such as those derived from pineapple leaves [20], okra stems [21], Sida cordifolia [22], Arundo donax [23], Lygeum spartum [24], Coccinia grandis [25], Markhamia lutea [26], Erythrina variegate [27] and Albizia Saman [28]. Concerning plant fibers issued from tropical plants in Central, East and West African countries, some studies are related to the identification of properties of African star apple leaves [29], Bast fibers of Triumfetta cordifolia [30] and Rhectophyllum camerunense fibers [31][32][33]. This paper concerns the mechanical properties of plant fiber extracted from the bark of Cola lepidota (CL) plant.…”
Section: Introductionmentioning
confidence: 99%